Validity of 4DCT determined internal target volumes in radiotherapy for free breathing lung cancer patients - Pinto, Marta Cristina Bravo de Moreira (2018)
Background: With both high incidence and death rate, lung cancer accounts for a large burden of disease worldwide. In many cases, these patients receive radiotherapy. Commonly, margins are added to the treatment volume to avoid underdosage due to the respiration-induced tumour motion. Four-Dimensional Computer Tomography (4DCT) is an imaging technique that is capable of capturing the lung tumours as they move during respiration, which enables the creation of individualized margins. However, the technique requires regular breathing during the entire scan to avoid breathing motion artefacts. Many patients do not fulfil this requirement. Moreover, there is also a substantial risk of encountering irregularities in the breathing pattern during the 4-8 minutes that are usually needed for treatment delivery. Hence, there is a potential risk of underestimating the tumour volume and its motion, i.e., the Internal Target Volume (ITV), for patients with irregular breathing patterns. We aim to investigate the risk of underestimating a 4DCT determined ITV due to irregular breathing patterns during a typical treatment period. Method: For 5 patients, the ITV was extracted from a 4DCT scan and compared to the ITV extracted in the sum of 150 cine images (3 x 50). The cine images were acquired during 4 minutes in three different sessions. All ITVs were obtained through segmentation. Results: It was found that ITVs obtained from the 4DCT scan were smaller than the ones from the cine images case, and the statistical analysis done confirmed this at a significance level of 5%. Conclusion: We conclude that the required margin to handle respiratory-induced tumour motion can be underestimated for patients with irregular breathing pattern if the ITV is based on a conventional treatment planning 4DCT. The main cause for this is inter-fractional variations.